Tobacco-related cancers in Europe: the scale of the epidemic in 2018 - Kulhánová, Ivana; Forman, David; Vignat, Jerome; Espina, Carolina; Brenner, Hermann; Storm, Hans H.; Bauld, Linda; Soerjomataram, Isabelle (European journal of cancer, 2020)
Background - Tobacco smoking is the major preventable cause of cancer. Despite the longstanding decline in smoking prevalence, lung cancer remains one of the most frequently diagnosed cancers in both sexes. We aimed to estimate the current cancer burden attributable to smoking in Europe. - Methods - Smoking-related cancer incidence by country, cancer type, sex and age in Europe was estimated from GLOBOCAN 2018. We applied a modified version of the indirect method to estimate the population attributable fraction (PAF) for lung cancer and applied Levin's formula to estimate the PAF for other smoking-related cancer sites. - Results - In Europe in 2018, 572,000 and 186,000 cancer cases were attributable to tobacco smoking in males and females respectively, accounting for 28% (males) and 10% (females) of all cancer cases. By region, the largest and the lowest PAF due to smoking in males occurred in Eastern Europe (35% of all cancer cases) and Northern Europe (21%), respectively. Among women, this pattern was reversed (16% in Northern Europe and 6% in Eastern Europe). Lung cancer accounted for more than half of the total cancer burden attributable to smoking (382,000). Other major contributors to the total PAF were lip, oral cavity and pharynx, bladder and laryngeal cancers in men (27% out of total PAF) and colorectal, pancreatic, oral cavity and pharyngeal cancers (21%) in women. - Conclusions - Tobacco smoking was responsible for one in five cancer cases in Europe in 2018. The introduction and robust implementation of tobacco control programmes are critical to reduce this cancer burden in the future.